2011
DOI: 10.1007/s00415-011-6205-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between clinical and pathological variables in Richardson’s syndrome

Abstract: In order to determine the relationship between regional neuropathology and severity of clinical features in Richardson's syndrome (PSP-RS), the following hypotheses were tested: (1) executive dysfunction relates to prefrontal pathology; (2) language difficulties to pathology in Broca's area and/or the perirhinal cortex; and (3) visuospatial impairment to pathology in the supramarginal region. A prospectively studied case series of brain donors at a specialist clinic in Addenbrooke's Hospital Cambridge, UK, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…E,F), with rates of mid‐brain loss estimated at approximately 3% per annum, compared to less than 0.5% in age‐matched controls . The distribution of atrophy from voxel‐based morphometry is less widespread than expected from the distribution of high pathological burden . The difference may reflect delays between participation in imaging studies and postmortem examination.…”
Section: Pathology and Imaging Substrates Of Cognitive Changementioning
confidence: 93%
See 1 more Smart Citation
“…E,F), with rates of mid‐brain loss estimated at approximately 3% per annum, compared to less than 0.5% in age‐matched controls . The distribution of atrophy from voxel‐based morphometry is less widespread than expected from the distribution of high pathological burden . The difference may reflect delays between participation in imaging studies and postmortem examination.…”
Section: Pathology and Imaging Substrates Of Cognitive Changementioning
confidence: 93%
“…The neuropathology of PSP is distinctive, with hyperphosphorylation and aggregation of the microtubule‐associated protein tau in the pallidum, subthalamic nucleus, red nucleus, substantia nigra, pontine tegmentum, striatum, oculomotor nucleus, medulla, and dentate nucleus . Cortical pathology is widespread, including neuronal loss and tau deposition in the superior frontal gyrus, the supramarginal gyrus extending along the superior temporal lobe . One of the consequences of PSP that may affect cognition is the change in critical neurotransmitters with PET and autoradiographic evidence for reductions of cortical gamma‐aminobutyric acid A receptors, acetylcholine, and monoamine vesicular transporters in the striatum and frontal cortex .…”
Section: Pathology and Imaging Substrates Of Cognitive Changementioning
confidence: 99%
“…All patients were classified according to the clinical variants of FTD at presentation, or within 6 months of presentation (Gorno-Tempini et al, 2011; Rascovsky et al, 2011). Patients were included in this study based on their current clinical diagnosis, which, from previous clinicopathological studies (Hodges et al, 2004; Schofield et al, 2012), have been demonstrated to be highly predictive (>75% accuracy) for either Tau or TDP-43 neuropathological inclusions at autopsy. We employed the FRS, which is capable of staging disease severity in FTD based upon functional dependence and behavioural changes (Mioshi et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The MAPT gene was the first FTD locus to be identified (reviewed in Sieben et al, 2012), and mutations in the gene encoding TDP-43 ( TARDBP ) can give rise to MND (Sreedharan et al, 2008) and FTD in rare instances (Borroni et al, 2010). Clinicopathological correlations have revealed that certain clinical subgroups are associated predominantly with either Tau or TDP-43 neuropathology, with all individuals with FTD-MND having TDP-43 immunopositive inclusions and most individuals with CBS, PSPS and PNFA having Tau inclusions at autopsy (Hodges et al, 2004; Schofield et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Subcortical (basal ganglia and basal forebrain) and frontal lobe pathology may both contribute to cognitive decline. Additionally, recent studies suggest that the disease also involves cortical areas outside the frontal lobe, such as the supramarginal gyrus 67. PSP and CBD share several pathological features, suggesting that the two diseases might belong to the same disease spectrum.…”
Section: Neuropathological Featuresmentioning
confidence: 99%